Improving The Seventh Grade Students’ Vocabulary Mastery at UPTD SMP Negeri 22 Barru by Using Telegram Application - Yuliati, Yuliati; Patahuddin, Patahuddin; Patintingan, Amir (La Parole : Journal of Language Teaching and Pedagogy, 2022)
Based on observation, the researcher found that students’ vocabulary mastery relatively low where the big triggers was the learning media used by teacher. So that, the objective of this researcher was to measure whether the use of telegram application can improve the seventh grade students’ vocabulary mastery at UPTD SMP Negeri 22 Barru. In this research the researcher applied quasi-experimental method.The population of this research was the seventh grade students at UPTD SMP Negeri 22 Barru. The samples of the research taken using cluster random sampling technique, there are two classes as sample, experimental class and control class, both classes consisted of 28 students.The data was collect using vocabulary test (pre-test and post-test) and analyze employ statistical calculation to test the hypothesis. The result of this research shows that the mean score of pre-test was 45.35 and the post-test was 83.57. Besides the different score of pre-test and post-test, the mean score of the students in post-test 83.57 is higher than the Kriteria Ketuntasan Minimal (75) in UPTD SMP Negeri 22 Barru. The result of t-test value in post-test was 2.214 and t-table value was 1.684. It means that H1 was accepted and H0 was rejected and The seventh grade students at UPTD SMP Negeri 22 Barru who are taught by using telegram application is have better vocabulary mastery than the seventh grade students who are taught without using telegram application.